2022
DOI: 10.1021/acsestengg.2c00178
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Band Structure of Crystalline Potassium Poly(heptazine imide) for Enhanced Photocatalytic H2O2Production and Pollutant Degradation

Abstract: The photocatalytic selective oxygen reduction reaction on a polymeric carbon nitride framework is one of the most promising approaches toward sustainable H2O2 production. Potassium poly­(heptazine imide) (K-PHI) was highly active for photocatalytic H2O2 production. Most importantly, by introducing 1-methyl-1H-tetrazole-5-thiol (MTT) into the precursor for the K-PHI synthesis, the size of the layer stacking structure was reduced, the polymerization in the heptazine plane was improved, and the conduction band po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…Additionally, a low pH could reduce the K + in the framework, which is critical for the photocatalytic performance. 22,30,41 We thus speculate that the photoresponse of the catalyst could be the key to the H 2 O 2 formation. Further increasing the pH to 11 significantly reduced the concentration of H 2 O 2 , which may be attributed to decreased stability of H 2 O 2 in such a basic environment.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Additionally, a low pH could reduce the K + in the framework, which is critical for the photocatalytic performance. 22,30,41 We thus speculate that the photoresponse of the catalyst could be the key to the H 2 O 2 formation. Further increasing the pH to 11 significantly reduced the concentration of H 2 O 2 , which may be attributed to decreased stability of H 2 O 2 in such a basic environment.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…On AT-CN, the photocatalytic production of H 2 O 2 was sensitively impacted by the pH of the suspension, and the basic environment with a pH of around 9.0–10.0 was the optimistic reaction condition, which indicated that the protonation step was not the rate-determining step for H 2 O 2 production. Additionally, a low pH could reduce the K + in the framework, which is critical for the photocatalytic performance. ,, We thus speculate that the photoresponse of the catalyst could be the key to the H 2 O 2 formation. Further increasing the pH to 11 significantly reduced the concentration of H 2 O 2 , which may be attributed to decreased stability of H 2 O 2 in such a basic environment.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The in-plane periodicity of ATC-CNK poses certain similarities to that in the potassium poly(heptazine imide) (K-PHI) nanocrystals due to the diffraction peaks at 8.1°for both ATC-CNK and K-PHI. 21,39,47 The shift of the (002) diffraction peak reveals that the spacing of the layer stacking is reduced by 0.01 nm after the incorporation of K + in the framework, indicating that the incorporation of K + could enhance the interaction between the layers. 4,48 Since the polymeric carbon nitride frameworks have low dielectric constant, and the excitons are localized in the heptazine unit and the polarons are hopping along the direction perpendicular to the heptazine unit via the overlapped molecular orbitals in Brownian motion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been frequently observed that the formation of the N-metal coordination bond in the CN framework will lead to a partial charge transfer from nitrogen to metal, and this charge transfer will cause the enhancement of the π* resonance peaks in the N K-edge XANES profile. 59,60 The enhancement of the π* resonance peaks herein is thus indicative of the perturbation 22 of the electronic structure via partial electron transfer from CN to the surface-complexed MV unit (Figure 2c).…”
Section: Mv-boosted Photocatalytic Production Of H 2 O 2 Onmentioning
confidence: 99%